Functional Tests and Surveys Used to Assess Nervous System Dysfunction in Patients with Fabry Disease – A Review - Stanislaw Jesionek; Jakub Parys; Agnieszka Mikosińska; Martyna Kaźmierczak; Partycja Kałuziak; Marta Jajczak; Maciej Mossakowski; Aleksandra Witek; Mateusz Litwin; Justyna Jankowska (Quality in Sport)
Introduction and Purpose: